2023
DOI: 10.1002/ardp.202300263
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the chemical profile, antioxidant, enzyme inhibitory, cytotoxic potential of different extracts from Astragalus caraganae

Abstract: Six extracts (water, ethanol, ethanol‐water, ethyl acetate, dichloromethane, and n‐hexane) of Astragalus caraganae were studied for their biological activities and bioactive contents. Based on high‐performance liquid chromatography‐mass spectrometry (HPLC‐MS), the ethanol‐water extract yielded the highest total bioactive content (4242.90 µg g−1), followed by the ethanol and water extracts (3721.24 and 3661.37 µg g−1, respectively), while the least total bioactive content was yielded by the hexane extract, foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 113 publications
0
12
0
Order By: Relevance
“…In this context, 100 µg/mL was chosen as the common concentration at which the extracts did not reduce cell viability below 60% at the same time points. [46] In studies conducted with different species of the Stachys genus in the literature, it has been observed that the genus effectively regulate cell proliferation due to its abundant secondary metabolites. [47][48][49][50] For instance, when Stachys parviflora was applied to the uncontrolled proliferation of breast cancer cell lines MCF-7 and MDA-MB-231, as well as the prostate cancer cell line PC3, it effectively inhibited cell proliferation and induced apoptosis.…”
Section: Determination Of Cytotoxicity and Cell Proliferation Effect ...mentioning
confidence: 99%
See 4 more Smart Citations
“…In this context, 100 µg/mL was chosen as the common concentration at which the extracts did not reduce cell viability below 60% at the same time points. [46] In studies conducted with different species of the Stachys genus in the literature, it has been observed that the genus effectively regulate cell proliferation due to its abundant secondary metabolites. [47][48][49][50] For instance, when Stachys parviflora was applied to the uncontrolled proliferation of breast cancer cell lines MCF-7 and MDA-MB-231, as well as the prostate cancer cell line PC3, it effectively inhibited cell proliferation and induced apoptosis.…”
Section: Determination Of Cytotoxicity and Cell Proliferation Effect ...mentioning
confidence: 99%
“…and demonstrate the effect of S. tundjeliensis on MMPs that may change accordingly. In this context, the ROS mechanism was activated by applying 75 µmol/L of H 2 O 2 to HDF cells for 2 h. [46,67] On the other hand, 250 µg/mL of EGCG was applied to H 2 O 2 -induced HDF cells for 48 h as a positive control. [46,67] In the gel image showing MMP-2 and MMP-9 activity in Figure 10a, active MMPs broke down their substrates in their respective areas and formed white lytic bands.…”
Section: Inhibition Activity Of Three Different Extracts Obtained Fro...mentioning
confidence: 99%
See 3 more Smart Citations